Representasi gender dalam filem bertema kepolisan / Jodie Yap Siew Wen - Jodie Yap , Siew Wen (2018)
Films can act as a medium to convey ideological stances. In action movies, it is common to find men and women represented using existing gender stereotypes. This study analyzes gender representation in the film Gerak Khas using the approaches of Van Leeuwen (2008), Bem (1981) dan Halliday (1994) In addition, the researcher also study whether the represented gender follow or challenge existing stereotypes. This study is a qualitative study through a Discourse Analysis approach that makes descriptive study. Findings shown that the women and men in those movies are represented as equals. In the cop films male characters are portrayed as masculine and there are also female characters where women were seen challenging the stereotypes and were trying to show that they can bear the same responsibility as men.